A teologia a partir do reverso da história: uma interpretação do modo de fazer teologia de Gustavo Gutiérrez - Bittencourt, Neusa Regina Carneiro (2012)
This dissertation focus on the reading of the history since its reverse, made possible through the Liberation Theology, a theology which emerged in Latin America within the broader path of Theology in the 20th century. This dissertation studies different phases in this path. Its main core is on the thought and works of Gustavo Gutiérrez, his method and the founding categories which were elaborated in the beginning of the Liberation Theology, also investigating authors who preceded him and were important in his theological options. The research analyzes how the author developed his great reflections, which stood out in the context of the Liberation Theology; aiming at the understanding and interpretation of the theological place of the poor ones and the Christian faith revelation, lived in the reverse of history, based on the reality faced by the poor ones, those who are not acknowledged in the official history.